2000
DOI: 10.1007/10720296_11
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Models of Personality and Emotions into Lifelike Characters

Abstract: Abstract.A growing number of research projects in academia and industry have recently started to develop lifelike agents as a new metaphor for highly personalised human-machine communication. A strong argument in favour of using such characters in the interface is the fact that they make humancomputer interaction more enjoyable and allow for communication styles common in human-human dialogue. Our earlier work in this area has concentrated on the development of animated presenters that show, explain, and verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 15 publications
0
74
0
2
Order By: Relevance
“…Although these features have been suggested by the psycholinguistic literature, reported correlations with personality ratings are generally weak: it was not obvious that they would improve accuracies of statistical models on unseen subjects. Computational work on modelling personality has primarily focused on methods for expressing personality in virtual agents and tutorial systems, and concepts related to personality such as politeness, emotion, or social intelligence (Walker, Cahn, & Whittaker, 1997;André, Klesen, Gebhard, Allen, & Rist, 1999;Lester, Towns, & FitzGerald, 1999;Wang, Johnson, Mayer, Rizzo, Shaw, & Collins, 2005) inter alia. Studies have shown that user evaluations of agent personality depend on the user's own personality (Reeves & Nass, 1996;Cassell & Bickmore, 2003), suggesting that an ability to model the user's personality is required.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Although these features have been suggested by the psycholinguistic literature, reported correlations with personality ratings are generally weak: it was not obvious that they would improve accuracies of statistical models on unseen subjects. Computational work on modelling personality has primarily focused on methods for expressing personality in virtual agents and tutorial systems, and concepts related to personality such as politeness, emotion, or social intelligence (Walker, Cahn, & Whittaker, 1997;André, Klesen, Gebhard, Allen, & Rist, 1999;Lester, Towns, & FitzGerald, 1999;Wang, Johnson, Mayer, Rizzo, Shaw, & Collins, 2005) inter alia. Studies have shown that user evaluations of agent personality depend on the user's own personality (Reeves & Nass, 1996;Cassell & Bickmore, 2003), suggesting that an ability to model the user's personality is required.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…This represents one aspect of a very significant effort to design emotion and personality models for agents (e.g. [2,17,10,38,32,1,15,31]). …”
Section: Discussionmentioning
confidence: 99%
“…Our use of coping preferences to guide choice of coping strategies or behaviors is similar to [3,11,22]. However, this past work has relied on emotions only and not personality based on experience to constrain decision-making.…”
Section: Future Work Discussion and Conclusionmentioning
confidence: 99%
“…However this is a time consuming and expensive approach, and not even feasible when large numbers of different characters are needed. Most prior work that aims to create characters with emotions and personality has concentrated on one or two characters (such as [3]) or superficial crowd simulations (such as [2]). …”
Section: Introductionmentioning
confidence: 99%